2018
DOI: 10.1155/2018/6541583
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicological Evaluation of Schinus molle L. (Anacardiaceae) Essential Oil in Lymphocytes and Macrophages

Abstract: Schinus molle L. is used to treat various diseases; however, the literature lacks information regarding its possible immunotoxic effects. The aim of the study was to investigate the immunotoxic effects of essential oil from leaves of Schinus molle L. in cultures of human lymphocytes and macrophages. The cultures were treated with essential oil (EO) of Schinus molle L. and subsequently subjected to genotoxic analysis (comet assay), mutagenic analysis (micronucleus frequency and chromosomal aberration), and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The in silico output also indicated that embelin has an immunotoxic property. Similar reports stated that plant-based natural products have the potential to possess an immunotoxicity effect [37] , [38] , [39] , [40] . This might be due to the possible effect of embelin on immune regulatory molecules such as PD-1 (programmed cell death 1), CTLA-4 (cytotoxic T-lymphocyte antigen 4), and galectins since there are evidences showing that medicinal plants have a potential of immune checkpoints inhibition [41] , [42] .…”
Section: Discussionmentioning
confidence: 52%
“…The in silico output also indicated that embelin has an immunotoxic property. Similar reports stated that plant-based natural products have the potential to possess an immunotoxicity effect [37] , [38] , [39] , [40] . This might be due to the possible effect of embelin on immune regulatory molecules such as PD-1 (programmed cell death 1), CTLA-4 (cytotoxic T-lymphocyte antigen 4), and galectins since there are evidences showing that medicinal plants have a potential of immune checkpoints inhibition [41] , [42] .…”
Section: Discussionmentioning
confidence: 52%
“…EO from the leaves of Schinus molle increased TNFα and nitric oxide production, reduced IL-10 production, and generated no change in the levels of IL-6 compared to negative controls in cultures of human lymphocytes and activated macrophages, altogether leading to an activation of the immune system [31]. EO extracts from various parts of Ferula iliensis dose-dependently enhanced superoxide anion production in isolated human neutrophils and bone marrow leukocytes from mice.…”
Section: In Vitro Investigationsmentioning
confidence: 88%
“…Allium sativum (garlic) [22] Eucalyptus globulus (eucalyptus) [23,24] eugenol (from Syzygium aromaticum, clove) [25,26] Ferula iliensis [27] frankincense EO (derived from Boswellia carterii) [28] Lavandula angustifolia (lavender) [29] Pituranthos tortuosus [30] Schinus molle [31] Syzygium cumini (jambolão) [32] Thymus vulgaris (thyme) [33] In Vivo Pre-Clinical Studies…”
Section: In Vitro Investigationsmentioning
confidence: 99%
“…S. molle EO has a promising application due to activity against Paracoccidioides brasiliensis, the etiologic agent of paracoccidioidomycosis (Do Prado et al 2018). Nonetheless, S. molle EO showed cytotoxicity in lymphocytes and macrophages, probably in function of the major compound ɑ-pinene because of oxidative stress, but the mechanism of cytotoxicity of ɑ-pinene remains unclear (Türkez & Aydin 2016, Duarte et al 2018.…”
Section: Schinusmentioning
confidence: 99%